S63 Postoperative pulmonary complications and physiotherapy requirements after open thoracotomy versus vats lobectomy: a propensity score-matched analysis. (15th November 2016) - Agostini, P; Lugg, ST; Adams, K; Vartsaba, N; Kalkat, M; Rajesh, PB; Steyn, RS; Naidu, B; Rushton, A; Bishay, E
Abstract : Introduction: Video-assisted thoracoscopic surgical (VATS) lobectomy is increasingly used for curative intent lung cancer surgery compared to open thoracotomy due to its minimally invasive approach and associated benefits. However, the effect of the VATS approach on postoperative pulmonary complications (PPC), rehabilitation and physiotherapy requirements is unclear; our study aimed to use propensity score matching to investigate this. Methods: Between January 2012 and January 2016 all consecutive patients undergoing lobectomy via thoracotomy or VATS were prospectively observed. Exclusion criteria included VATS converted to thoracotomy, re-do thoracotomy, sleeve/bi-lobectomy and tumour size >7 cm diameter (T3/T4). All patients received physiotherapy assessment on postoperative day 1 (POD1), and subsequent treatment as deemed appropriate. PPC frequency was measured daily using the Melbourne Group Scale. 1 Postoperative length of stay (LOS), high dependency unit (HDU) LOS, intensive therapy unit (ITU) admission and in-hospital mortality were observed. Propensity score matching (PSM) was performed using previous identified PPC risk factors (age, ASA score, BMI, COPD, current smoking) and lung cancer staging. Results: Over 4 years 736 patients underwent lobectomy with 524 remaining after exclusions; 252 (48%) thoracotomy and 272 (52%) VATS cases. PSM produced 215 matched pairs. VATS approach was associated with less PPC (7.4% Vs 18.6%; p < 0.001), shorter median LOS (4 days vs 6; p < 0.001), and a shorter median HDU LOS (1 day vs 2; p = 0.002) (Table 1 ). Patients undergoing VATS required less physiotherapy contacts (3 Vs 6; p < 0.001) and reduced therapy time (80 min vs 140; p < 0.001). More patients mobilised on POD1 (84% vs 81%; p = 0.018), and significantly less therapies to treat sputum retention and lung expansion were required (p < 0.05). Conclusions: This study demonstrates that patients undergoing VATS lobectomy developed less PPC and had improved associated outcomes compared to thoracotomy. Patients were more mobile earlier, required half the physiotherapy resources, having fewer pulmonary and mobility issues. Reference: Agostini P, et al . Postoperative pulmonary complications following thoracic surgery: are there any modifiable risk factors? Thorax 2010;65 (9):815–8.